Enhanced stability of pulverized biomass flames using an expanded primary port with bluff body - Laphirattanakul, Ponepen; Siripoom, Pongsakorn; Keawchompoo, Chatchalerm; Charoensuk, Jarruwat (My University, 2026)
The impact of bluff body geometry combined with primary exit port expansion on the flame stability of a biomass pulverized fuel burner was investigated through numerical simulations. The expansions, applied at 1.25 and 1.5 times the original port size while maintaining a constant blockage ratio, were intended to reduce the momentum ratio between primary and secondary air streams. However, this adjustment concurrently led to a decrease in the swirl number, primarily due to the reduction in the secondary air exit area. Experimental results from the base case configuration were employed for model validation. Among the turbulence models considered, the SST k-ω model demonstrated the best agreement with experimental data in terms of temperature distribution and emission characteristics. The simulation results revealed that the base case exhibited flame anchoring behind the bluff body, supported by a pronounced reverse velocity region in its wake. Flame stability was also achieved in the 1.5SB case, attributed to a sufficiently reduced momentum ratio. This reduction enhanced the entrainment of the secondary air stream, promoting greater dispersion of fuel particles and enabling early-stage volatile combustion. The 1.5SB configuration achieved the highest temperature among all cases, reaching approximately 1150 °C. In contrast, the 1.25SB case exhibited flame blowout, resulting from a combination of reduced swirl number and an insufficient reduction in momentum ratio.
Keywords: Biomass; Momentum ratio; Swirl